Perancangan Sistem Informasi Penilaian Kinerja Guru Di SMK Negeri 10 Bungo - Lamsari Harahap; Faiza Rini; Haris Kurniawan (Unversitas Muhammadiyah Mataram, 2025)
Abstract: The teacher performance evaluation process at SMK Negeri 10 Bungo has so far been carried out manually, which results in the process taking a relatively long time and the resulting data is difficult to use for continuous performance evaluation. This poses a challenge in ensuring that the teacher performance evaluation process is carried out efficiently, quickly, and accurately Therefore, this study aims to design a systematic and computerized teacher performance assessment information system using the System Development Life Cycle (SDLC) method. This research was conducted using Visual Studio Code as the development editor and the PHP 8 programming language. The results of this study are the Design of a Teacher Performance Assessment Information System with an iterative model consisting of six stages: planning, analysis, design, implementation, testing, and management. System testing is divided into two stages, namely Alpha testing (which includes whitebox and blackbox testing) and Beta testing by experts and users. The results of the Beta test show that the validation carried out by system experts obtained an average score of 88.5%, with the description